A non-targeted proteomics investigation of cylindrospermopsin-induced hepatotoxicity - González Blanco, Carlos Andrey (2017)
Cyanobacteria is perhaps the phylum that profit the most from the escalating hypereutrophication of continental waters. The resulting cyanobacterial blooms may accumulate a variety of potent toxins. Cylindrospermopsin (CYN) is a cyanotoxin known for inhibiting protein synthesis, and producing oxidative stress as well as DNA damage in eukaryotic cells. Since the toxin\'s molecular mechanisms and targets are still unclear, we purified the cyanotoxin from our lab strains and employed a shotgun proteomics approach to reveal the major changes in HepG2 cells at sublethal doses of CYN (1 µM for 6, 12 and 24h). Metabolically labeled cells were stimulated and lysed after each treatment, their tryptic digests were separated by nano HPLC and analyzed by high-resolution tandem mass spectrometry (HRMS) on data dependent acquisition mode. We scanned an average of 4000 proteins in every sample throughout the three timepoints. Cholesterol biosynthesis and transport was mostly downregulated throughout the timepooints of the experiment. Downregulation of proteins related to ubiquitination (e.g. UBE2L3) and proteolysis pathways (e.g. PSMA2) was observed in the proteomics dataset, and these results were validated by western blot. Transcription, translation and cell cycle processes showed convoluted regulation dynamics involving known cell cycle regulators like PCNA. Downregulation of mitochondrial enzymes, oxidative stress and damage to the mithochondrial inner membrane was early evidenced after a 6 hrs treatment and validated using a JC-1, a mitochondrial membrane potential probe. The resulting dataset gives us a first glimpse of the protein groups affected at the early stage of CYN cell intoxication.